identifikasi kompleks makam kuno wakil kapita malaka di kelurahan anduonohu kecamatan poasia kota kendari - Asep Nugraha Asep (SANGIA: Jurnal Penelitian Arkeologi, 2019)
ABSTRACT Asep Nugraha, "Identification of the Ancient Tomb Complex of Deputy Kapita Malaka in Anduonohu ​​Sub-District, Poasia District, Kendari City" guided by H. Abdul Rauf Suleiman and Syahrun. The purpose of this study is to find out what forms of tomb and culture affect the tomb. The research method used is descriptive analysis which consists of several stages namely surface survey, interview, observation, documentation and then added with morphological analysis. the results of this study were that the site of the ancient tomb complex of Deputy Kapita Malaka in Anduonohu ​​Village, Poasia District, Kendari City was generally square in shape, which was later built using earth mounds, had tombs and tombstones. There are 4 types of tombs based on the shape of the tomb, namely types A1, A2, A3 and A4, and there are 3 forms of gravestones, namely types PS, LJ, and TB. Based on the shape of the tomb, as well as its history, it can be concluded that the ancient tomb complex of Deputy Kapita Malaka is an Islamic tomb that is still influenced by the megalithic tradition. Keywords: Graveyard, Nisan, Culture